PENGARUH PEMBERIAN KOMPOS ISI RUMEN SAPI TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Mona Gusvita Sari; Edison Anom; Arnis En Yulia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research was to know the effect of giving compost contains cow rumen and get a dose of composted cow rumen content on seedling growth of the cocoa plant(Theobroma cacao L.). This research had been conducted on the experimental field of the Faculty of Agriculture, University of Riau from April to August 2015. This research was conducted in the form of non-factorial experiment arranged in the form of completely randomized design (CRD), which consists of 5 treatment with each dose of composted cow rumen contents that (K0 ): without composted cow rumen contents, (K1): 25 g/plant (K2): 50 g/plant, (K3): 75 g/plant and (K4): 100 g/plant. Each unit treatment was repeated 4 times to obtain 20 units of the experiment and the experimental unit comprises three plants, two of which are used as plant samples. Parameters measured were seedling height, stem diameter, number of leaves, leaf area, root volume, the ratio of crown roots and dry weight. Results of the analysis will be followed by a test of Duncan New Multiple Range Test (DNMRT) at 5%. Giving Composting cow rumen content with a dose of 50 g/plant, 75 g/plant and 100 g/plant gave outgrowth good cocoa crop seeds in the parameter leaf area, root volume, the ratio of crown roots and dry weight of seedlings.   Keywords :compost, cow rumen contents, seeds, cocoa.